Economic evaluation of increasing population rates of cardiac catheterization - Clement Fiona M; Ghali William A; Rinfret Stephane; Manns Braden J (BMC, 2011)
Abstract Background Increasing population rates of cardiac catheterization can lead to the detection of more people with high risk coronary disease and opportunity for subsequent revascularization. However, such a strategy should only be undertaken if it is cost-effective. Methods Based on data from a cohort of patients undergoing cardiac catheterization, and efficacy data from clinical trials, we used a Markov model that considered 1) the yield of high-risk cases as the catheterization rate increases, 2) the long-term survival, quality of life and costs for patients with high risk disease, and 3) the impact of revascularization on survival, quality of life and costs. The cost per quality-adjusted life year was calculated overall, and by indication, age, and sex subgroups. Results Increasing the catheterization rate was associated with a cost per QALY of CAN$26,470. The cost per QALY was most attractive in females with Acute Coronary Syndromes (ACS) ($20,320 per QALY gained), and for ACS patients over 75 years of age ($16,538 per QALY gained). However, there is significant model uncertainty associated with the efficacy of revascularization. Conclusion A strategy of increasing cardiac catheterization rates among eligible patients is associated with a cost per QALY similar to that of other funded interventions. However, there is significant model uncertainty. A decision to increase population rates of catheterization requires consideration of the accompanying opportunity costs, and careful thought towards the most appropriate strategy.